Freak Observers and the Simulation Argument. (26th June 2013) - Crawford, Lyle
Abstract: The simulation hypothesis claims that the whole observable universe, including us, is a computer simulation implemented by technologically advanced beings for an unknown purpose. The simulation argument (as I reconstruct it) is an argument for this hypothesis with moderately plausible premises. I develop two lines of objection to the simulation argument. The first takes the form of a structurally similar argument for a conflicting conclusion, the claim that I am a so‐called freak observer, formed spontaneously in a quantum or thermodynamic fluctuation rather than through ordinary processes of evolution and growth. The second rejects the basic line of reasoning of both arguments: the sort of evidence they cite is not capable of supporting either the claim that I am a simulant or the claim that I am a freak observer. The evidence that simulants or freak observers exist is not a reason to think that I am one of them.